An integrative assessment of the diversity, phylogeny, distribution, and conservation of the terrestrial reptiles (Sauropsida, Squamata) of the United Arab Emirates - Burriel-Carranza, Bernat; Tarroso, Pedro; Els, Johannes; Gardner, Andrew; Soorae, Pritpal; Mohammed, Ahmed Ali; Tubati, Sai Ravi Krishna; Eltayeb, Mohamed Mustafa; Shah, Junid Nazeer; Tejero-Cicuéndez, Héctor; Simó-Riudalbas, Marc; Pleguezuelos, Juan Manuel; et al. (PloS one, 2019)
In the present study we use an unprecedented database of 5,535 distributional records to infer the diversity, ecological preferences and spatial distribution of the 60 species of terrestrial reptiles of the United Arab Emirates (UAE), and use the 57 native species to test the effectiveness of the protected areas' network in conserving this unique vertebrate fauna. We infer a time-calibrated phylogeny with 146 species of squamates and 15 genes including all UAE terrestrial reptile species to determine the phylogenetic diversity (PD) and evolutionary distinctiveness (ED) of the native species and to compare it with the distribution of the hotspots of native species richness. The results of this study indicate that the sampling effort is remarkable, covering 75% of the country's territory representing nearly the entire climatic space of the UAE defined by the mean annual temperature and the total annual precipitation, as well as the multivariate climatic space defined by a principal component analysis (PCA). Species richness is highest in the northeast of the country, in a transitional area from sandy desert to the mountainous terrain of the Hajar Mountains. The highest PD of a single square cell of 10 arc-minutes grid is of 2,430 million years (my) of accumulated evolutionary history and the strong correlation between PD and species richness suggests that the raw number of species is a good surrogate to quantify the evolutionary history (i.e., PD). The species with the highest values of ED are those in families represented by only one species in the UAE. Finally, the assessment of the UAE protected areas shows that, despite their relevance in protecting the terrestrial reptiles, they do not offer adequate protection for some threatened species. Therefore, a reassessment of some of the protected areas or the creation of species specific conservation action plans are recommended in order to ensure the preservation of the unique diversity of UAE terrestrial reptiles.
Keywords: Species Specificity; ohrožené druhy; Biological Evolution; Conservation of Natural Resources; Lizards; Spojené arabské emiráty; Animals; Endangered Species; United Arab Emirates; biodiverzita; zachování přírodních zdrojů; druhová specificita; Phylogeny; zvířata; fylogeneze; biologická evoluce; ještěři; Biodiversity